ANALISIS YURIDIS DALAM PENETAPAN NOMOR: 0664/Pdt.P/2017/PA.PMK SEBAGAI PERLINDUNGAN HUKUM ASET WAKAF TIDAK TERCATAT DI MADURA - Merinda Cahya Muria Putri; Muttaqin Choiri (Universitas Islam Malang, 2022)
The practice of waqf in Madura is still dominated by legal acts of waqf whose object of waqf is land, as contained in the Waqf Information System. However, in practice it’s still found that waqf is carried out underground. The public's reluctance to do waqf officially causes the waqf assets to not have authentic evidence in the form of waqf land certificates. The purpose of the study was to analyze the legal protection efforts for unregistered waqf assets in Madura through the filing of a Itsbat Waqf case at the Religious Courts as in the determination of the Pamekasan Religious Court Number: 0664/Pdt.P/2017/PA.Pmk regarding Itsbat Waqf. The research method used is qualitative with a normative juridical approach and secondary data sources are primary legal materials and secondary legal materials. The results of this study indicate that before the enactment of Law Number 41 of 2004 concerning Waqf, legal acts of waqf in Madura which are not known to meet the administrative requirements of waqf can cause conflicts or disputes and can interfere with the process of utilizing waqf assets. The Religious Courts as the executor of judicial power should be able to make proactive efforts in safeguarding unrecorded waqf assets through the application for the Itsbat Waqf case. This research has limitations because it was conducted through a literature review alone, so research is needed through a field study.